2020
DOI: 10.1089/hum.2019.329
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Gene Therapy for Familial Hemophagocytic Lymphohistiocytosis Type 3, Caused by UNC13D Genetic Defects

Abstract: Familial hemophagocytic lymphohistiocytosis type 3 (FHL3) is a rare disease caused by mutations to the UNC13D gene and the subsequent absence or decreased activity of the Munc13-4 protein. Munc13-4 is essential for the exocytosis of perforin and granzyme containing granules from cytotoxic cells. Without it, these cells are able to recognize an immunological insult but are unable to execute their cytotoxic functions. The result is a hyperinflammatory state that, if left untreated, is fatal. At present, the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 66 publications
(101 reference statements)
1
16
0
Order By: Relevance
“…Overall, as both alpha-and gammaretroviral vectors are clinically applicable and have been used in X-SCID and CAR-T cell therapy 73,74 these data provide evidence for a proof of concept T cell gene therapy approach for fHLH3 as a bridge to transplant option. 75 Taking into account potential limitations of using retroviral vectors that are only able to efficiently transduce dividing cells, a recent study published by Takushi et al 76 has demonstrated lentiviral-mediated restoration of Munc13-4 protein expression and functionality in patientderived T cells (alongside HSCs derived from the equivalent Jinx murine model). Having tested different promoter elements including the murine MND viral promoter, the SIN-LV containing the EFS promoter and a codon-optimised UNC13D transgene performed most favourably in activated patient T cells and restored in vitro degranulation.…”
Section: Familial Hlhmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, as both alpha-and gammaretroviral vectors are clinically applicable and have been used in X-SCID and CAR-T cell therapy 73,74 these data provide evidence for a proof of concept T cell gene therapy approach for fHLH3 as a bridge to transplant option. 75 Taking into account potential limitations of using retroviral vectors that are only able to efficiently transduce dividing cells, a recent study published by Takushi et al 76 has demonstrated lentiviral-mediated restoration of Munc13-4 protein expression and functionality in patientderived T cells (alongside HSCs derived from the equivalent Jinx murine model). Having tested different promoter elements including the murine MND viral promoter, the SIN-LV containing the EFS promoter and a codon-optimised UNC13D transgene performed most favourably in activated patient T cells and restored in vitro degranulation.…”
Section: Familial Hlhmentioning
confidence: 99%
“…Through competitive repopulation assays the group established that degranulation reaches wild-type levels with 15% peripheral wild-type cells in the Jinx model; a feasible target for T cell gene therapy and although this work focused on an HSC approach it was suggested that gene-corrected T cells could offer a therapeutic option to reduce inflammation prior to HSCT. 76 It will likely remain a major challenge to collect autologous hyperactivated T cells for gene modification and reinfusion to achieve remission in HLH. It will be critical to understand whether infused T cells will persist and avoid exhaustion to mount viral challenges in a long-term setting.…”
Section: Familial Hlhmentioning
confidence: 99%
See 2 more Smart Citations
“…It is caused by mutations in UNC13D, encoding protein unc-13 homolog D (Munc 13-4), which is essential for priming perforin-containing vesicles for exocytosis; cells without functional protein cannot degranulate properly giving rise to the cytotoxic defect. Several groups have investigated gene correction using SIN γRV, 162 SIN alpharetrovirus, 163 or LV vectors, 164 noting functional restoration of degranulation activity in vitro and in vivo murine models. Gene-corrected T cells have also been investigated as an alternative therapeutic.…”
Section: Gene Therapy For Primary Immune Deficiencies: Future Perspectivesmentioning
confidence: 99%